Input here - Execute there through networks: the case of gaming - Christos Bouras; Vassilis Poulopoulos; Vassilis Tsogkas; Ioannis Sengounis (The 15th Workshop on Local and Metropolitan Area Networks (LANMAN 2007), Princeton, NJ, USA, 2007)
As the evolution of computer technology introduces new advances in networks (among others), online gaming becomes a new trend. Following the trends of our era, Games At Large introduces an innovative platform for running interactive, rich content multimedia applications over a WAN Network. Games@Large project?s vision is to provide a new system architecture for Interactive Multimedia which will enhance existing CE devices such as, Set Top Boxes (STB) and other devices, which are lacking both the CPU power and the graphical performance to provide a rich user experience. This paper presents the controllers? sub-system of the innovative mechanism that will be implemented in the context of Games at Large project. More specifically, it presents the general architecture of the complete system and focuses on the “capturing” and “execution of commands” modules at the client and server side. The client software captures the input from the input devices, sends the commands over a WAN and the server is responsible for receiving and executing the commands to the correct application.